Strategi Komunikasi Dakwah dalam Upaya Deradikalisasi Kelompok Islam Garis Keras di Indonesia - Purwosunu, Sutiono; Hermansah, Tantan; Fanshoby, Muhammad; Nur Rahman, Wildian Fajrin (Faculty of Dakwah and Communication, UIN Syarif Hidayatullah Jakarta, 2025)
This study aims to analyze the role of dakwah (Islamic preaching) as a communication strategy in the deradicalization of hardline Islamic groups in Indonesia. Using a qualitative descriptive approach and a library research method, this study examines various academic sources, official reports, and religious organization publications through thematic analysis. The findings reveal that dakwah, when framed as persuasive communication, functions as an ideological intervention that promotes awareness, empathy, and social reintegration. The study identifies three strategic stages of dakwah-based deradicalization: preventive (education and public awareness), curative (dialogue and spiritual counseling), and rehabilitative (social and economic reintegration). The effectiveness of these strategies depends on three key elements: the communicator’s credibility, the persuasiveness of the message, and the participatory nature of communication. This research offers a new perspective by positioning dakwah not merely as a religious ritual, but as a transformative communication tool, an instrument of soft power that strengthens Islamic moderation and social peace in Indonesia. Radikalisme keagamaan tetap menjadi ancaman nyata di Indonesia, yang semakin mengkhawatirkan dengan maraknya radikalisasi pada generasi muda. Penelitian ini menganalisis strategi komunikasi dakwah sebagai instrumen deradikalisasi yang efektif bagi kelompok Islam garis keras. Dengan metode studi pustaka dan analisis tematik terhadap berbagai sumber akademik dan laporan resmi, temuan penelitian mengungkap bahwa dakwah yang dirancang sebagai komunikasi persuasif berperan strategis pada 3 tahap yaitu preventif, kuratif , dan rehabilitatif. Studi ini menegaskan bahwa dakwah tidak hanya berfungsi sebagai penyampai ajaran, tetapi lebih sebagai instrumen komunikasi ideologis yang memfasilitasi perubahan kesadaran, empati sosial, dan transformasi keyakinan secara sukarela. Dengan memposisikan dakwah dalam kerangka strategi komunikasi, artikel ini menawarkan perspektif baru sebagai respons terhadap tantangan deradikalisasi yang kian kompleks.